2009
DOI: 10.1017/s1368980008004618
|View full text |Cite|
|
Sign up to set email alerts
|

Adolescent dietary patterns are associated with lifestyle and family psycho-social factors

Abstract: Objective: Dietary intake during adolescence contributes to lifelong eating habits and the development of early risk factors for disease in adulthood. Few studies have examined the dietary patterns of adolescents and the social and environmental factors that may affect them during this life stage. The present study describes dietary patterns in a cohort of adolescents and examines their associations with socioeconomic factors, as well as parental and adolescent risk factor behaviours. Design: A semi-quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
179
1
10

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(216 citation statements)
references
References 35 publications
26
179
1
10
Order By: Relevance
“…Although food intake studies have limitations, such as memory bias, classification, and quantification, and because the present study is cross-sectional, thereby preventing: the establishment of causal relationships; the contemplation of the temporal sequence of exposure and effect; and the subjectivity associated with factor analysis and the number of study factors 9,19 ; the results confirm that socioeconomic conditions determine dietary patterns 15,18,25 .…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Although food intake studies have limitations, such as memory bias, classification, and quantification, and because the present study is cross-sectional, thereby preventing: the establishment of causal relationships; the contemplation of the temporal sequence of exposure and effect; and the subjectivity associated with factor analysis and the number of study factors 9,19 ; the results confirm that socioeconomic conditions determine dietary patterns 15,18,25 .…”
Section: Discussionsupporting
confidence: 50%
“…In Western Australia, Ambrosini et al 15 found that low income was associated with the Western diet in 14-year-old adolescents. Low food availability is often due to low income, which usually has a negative impact on the amount and quality of the foods consumed by poor families 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the role of the family cannot be dismissed considering that a healthy diet is related to a better functioning family. 41,42 Parents of individuals with ADHD often report a more dysfunctional family environment, 39,43,44 so it is plausible that the relationship between low adherence to a healthy diet and ADHD diagnosis may be exacerbated by a dysfunctional a Dairy products include milk, cheese, yogurt, milk/ice cream, and dairy-based desserts; cereals include pasta, rice, potatoes, and breakfast cereals; bakery includes cookies, muffi ns, donuts, croissants, etc; vegetables (raw and cooked) include salads, tomatoes, spinach, broccoli, green beans, etc; citrus fruit include orange, mandarin, and kiwi; other fruit include apples, bananas, pears, etc; meat includes pork, chicken, beef, lamb, sausages, etc; fatty fi sh includes sardines, anchovies, tuna, mackerel, salmon, etc; white fi sh includes hake, codfi sh, etc; noncola soft drinks include lemon, orange, and other fl avors of soda drinks (all caffeine-free); and cola drinks include regular and diet cola drinks. b Seventy-two percent of cases and 80% of controls for noncola soft-drink consumers also drank cola.…”
Section: Discussionmentioning
confidence: 99%
“…One hundred different foods (g/d) were obtained from the FFQ and were assigned into thirty-three food groups (g/d), based on a previous Australian study (19) and used for analysis.…”
Section: Dietary Intakes and Food Group Consumptionmentioning
confidence: 99%